Improving problem-solving skills with worksheets using the discovery learning model-assisted quick response code - Nidaul Himmah; Edwin Musdi (SAINTIS Publishing, 2022)
Good teaching materials have an impact on the quality of mathematics learning and can help students become more engaged in their learning and develop their problem-solving skills. It is necessary to develop LKPD utilizing a discovery learning paradigm helped by QR codes in order to boost problem-solving abilities. This study uses a reliable and useful discovery learning paradigm with the use of a QR code to identify the characteristics of LKPD. The Plomp model, which has three steps total—the preparatory stage, the development stage, and the assessment—is used in this particular sort of study, which is called development research. For class VIII of junior high school, LKPD employs a discovery learning methodology with the use of a QR code. The tools employed are validation sheets, observation sheets, questionnaires, interviews, and final exams. The findings demonstrated the validity, applicability, and efficacy of the LKPD for class VIII junior high school students using the discovery learning approach. LKPD practicality was 87%, while LKPD validity was 89%. The average student score on tests measuring their ability to solve mathematical problems was 92%, which indicates the success of the program.